(untitled) - Keene, Donald (New York, 1955)
Including the poetry from the "Manyoshu"; legends from the "Kojiki"; selections from "The Tale of Genji," "The Pillow of Heike"; Noh Plays and Folk Songs; Stories by Saikaku and Haiku by Basho; Kabuki plays by Ikkyu and many other represetative works of Japanese literature.
Keywords: Japanese literature; Translations into english